Curso Bimodal Práctica Clínica de Enfermería Basada en la Evidencia: Alcances y Limitaciones. - Ligia Rojas Valenciano (Universidad de Costa Rica, 2011)
His article has as aim present the digest of entry of the performers of the bimodal course clinical Practice based on the evidence, as well as the final evaluation. The population was shaped to the beginning of the course by 23 persons, 20 nurses (you) of different public as private institutions of health and three students of fifth year of the career of Master in Infirmary of the University of Costa Rica. 8 professional tutors took part. The course was completed by 16 participants. There was in use the platform Dokeos, with a conference presencial monthly. The course lasted nine months. Diverse strategies of education were implemented. Result: the knowledge deteriorates as well as the clinical practice and it is necessary to be kept informed with results proceeding from the best scientific available evidence. It is a responsibility of every professional of the health to be updated. This way manifesto the group of performers in the course that was offered on clinical practice based on the evidence. The nurses and nurses, are conscious of this need and want to strengthen his practice to offer a quality attention; besides that it is by means of the investigation in his labor field that they it can and must manage. Conclusion: The clinical practice based on the evidence in a necessary tool, where his application is justified by the biotechnological advances accelerated in the area of the health, this forces the professional of Infirmary to be kept informed about the best practices in health to answer with responsibility to the population by means of the development of an updated and trustworthy practice, which it should induce to the capture of the best decisions in his professional occupation.